New-day statistical thinking: A bold proposal for a radical change in practices - van Witteloostuijn, Arjen (Journal of International Business Studies, 2020)
Abstract In this commentary, I argue why we should stop engaging in null hypothesis statistical significance testing altogether. Artificial and misleading it may be, but we know how to play the p value threshold and null hypothesis-testing game. We feel secure; we love the certainty. The fly in the ointment is that the conventions have led to questionable research practices. Wasserstein, Schirm, & Lazar (Am Stat 73(sup1):1–19, 2019. 10.1080/00031305.2019.1583913 ) explain why, in their thought-provoking editorial introducing a special issue of The American Statistician : “As ‘statistical significance’ is used less, statistical thinking will be used more.” Perhaps we empirical researchers can together find a way to work ourselves out of the straitjacket that binds us.